Slovenian Cross-Cultural Adaptation and Validation of Health-Related Quality of Life Measures for Chronic Otitis Media (COMQ-12), Vertigo (DHI, NVI) and TINNITUS (THI) - Vozel Domen; Steiner Nejc; Božanić Urbančič Nina; Mladenov Dejan; Battelino Saba (Sciendo, 2020)
To provide physicians and patients with the tools needed to evaluate patients' problems and health-related quality of life by cross-culturally adapting and validating the Chronic Otitis Media Questionnaire 12 (COMQ-12), the Dizziness Handicap Inventory (DHI), the Neuropsychological Vertigo Inventory (NVI) and the Tinnitus Handicap Inventory (THI).